Benefits of effective multidisciplinary teamwork: catheter ablation of premature ventricular ectopics. Issue 5 (20th May 2020) - Daveney, John; Nguyen, Thomas; Wright, Matt
Abstract : The case concerns a difficult but successful right ventricular outflow tract ectopy catheter ablation in a fit and well 33-year-old man with a 16-year history of symptomatic premature ventricular contractions (PVCs). Beta blockade medication had become ineffective in suppressing the PVCs, and a 24-hour Holter monitor revealed a high burden of ectopy (10%). An echocardiogram and cardiac MRI showed a structurally normal heart. During the procedure, it became impossible to uncurve the catheter, and it lodged in the patient's right femoral artery. Immediate collaboration with interventional cardiology and interventional radiology was required to resolve the issue. The case demonstrates that excellent teamwork and calling rapidly on input from subspecialties are integral to overcoming unexpected events and to achieve a safe and successful outcome. The patient involved was a medical student at the time and as one of the coauthors offers a unique insight.